Neurophysiological features of primary lateral sclerosis - de Carvalho, M; Kiernan, MC; Pullman, SL; Rezenia, K; Turner, M; Simmons, Z (Taylor and Francis, 2021)
Primary lateral sclerosis (PLS) is a motor neuron disease characterized by spinobulbar spasticity, absence of progressive lower motor neuron (LMN) dysfunction and marked by a slow functional decline. Electromyography is essential to exclude significant LMN involvement, particularly in the context of distinguishing PLS from amyotrophic lateral sclerosis (ALS), given that the prognosis is substantially better, and respiratory complications are unusual, in PLS. Nevertheless, minor neurogenic changes and occasional fasciculation potentials can be observed in PLS. The most useful technique for the objective assessment of upper motor neuron (UMN) dysfunction is transcranial magnetic stimulation (TMS), which in PLS is characterized by a high cortical threshold and delayed central conduction times. TMS is sensitive to identify cortical dysfunction in PLS and might have potential for monitoring UMN function in longitudinal studies and in clinical trials. The findings of TMS need to be interpreted in the context of the clinical presentation and phenotype, particularly in the differentiation between PLS and ALS. While other neurophysiological techniques have been investigated, studies to date have tended to involve small patient cohorts and as such, their value in distinguishing PLS from ALS remains unclear.